Determination of suitable co-precipitator (clarifying agents) for identifying the presence of rotenone from Derris elliptica - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A.; Ramli, M. K. A.; Latip, R.; Nordin, N. I. A. (2004)
Rotenone and its congeners have come into increasingly widespread usage as the active constituents of a large number of insecticides. The roots of Derris elliptica or tuba plant are used as a source of insecticidal compounds, primarily rotenone. The main objective of this work is to obtain the best co-precipitator and its optimal concentration in order to identify the appearances of rotenone in the extraction process. Rotenone was extracted from Derris elliptica root using two solvent systems: (1) Methanol 95 % (v/v) and (2) a mixture of methanol: H2O (8:2). The extraction was followed with the precipitation process using aluminium sulphate (1.5M) and the addition of co-precipitator (clarifying agents) such as calcium hydroxide, sodium carbonate, sodium caseinate and kieselguhr (diatomaceous earth) with 1M, 2M and 3M respectively. From the result obtained, it was found that calcium hydroxide was the best co-precipitator with the highest yield of 38.65 % (w/w) at an optimal concentration of 3M (mol/liter). The presence of rotenone was confirmed by using qualitative analysis of Thin Layer Chromatography (TLC).